Vectors of Violence: Legitimation and Distribution of State Power in the _People’s Liberation Army Daily_ (_Jiefangjun Bao_), 1956-1989 - Aaron Gilkison; Maciej Kurzynski (Journal of Cultural Analytics)
From personal memoirs and cooking recipes to revolutionary agitation and war coverage, the *People’s Liberation Army Daily* offers a wealth of insights into the sociopolitical and affective realities of post-1949 China. One of the few major periodicals that continued publication during the Cultural Revolution (1966-1976), the journal has received relatively scant attention from scholars, except for political science studies devoted to the PRC propaganda system. Combining close reading and historical analysis with quantitative conceptuality and text mining, we demonstrate how the *PLA Daily* legitimizes state violence differently through its representation of various soldier figures, the *zhanshi*, the *junren*, and the *minbing*. We also use a large language model to show how the journal distributes violent sentiments to international topics in times of domestic turmoil.